When the Mayor sees the Town hall butt… - Papadima, Aspasia (My University, 2023)
Brief of the Exhibition Call: "The town hall butt — Numerous stone sculptures are characteristic for the historical town hall in Bardejov. They go also alongside the renaissance oriel, where you can find the most bizarre one — a little boy with his head between his legs, protruding his naked butt into the square. The boy’s butt faces the house where, allegedly, the mayor used to live. According to a legend, it was a peculiar revenge on the town council for refusing to pay the builders of the town hall even though they had done their work well and on time. As the story goes, one of the builders placed the sculpture near the oriel and thus finished the work under cover of night."
Keywords: Poster; International Poster Exhibition; City of Bardejov 2